1976
DOI: 10.1021/bi00669a004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular control of membrane properties during temperature acclimation. Fatty acid desaturase regulation of membrane fluidity in acclimating Tetrahymena cells

Abstract: This is a study of the molecular mechanisms employed by Tetrahymena pyriformis to change the lipid composition and thereby the fluidity of its various membranes during temperature acclimation. By quantitatively measuring the intramembrane particle aggregation using freeze-fracture electron microscopy, membrane physical properties in 39.5 degrees C grown cells shifted to 15 degrees C were found to be correlated with the degree of phospholipid fatty acid desaturation. Alteration of the phospholipid polar head gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
1

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(80 citation statements)
references
References 36 publications
5
74
1
Order By: Relevance
“…The Q10 of the rhythm below 220C was 2.2, and periods of about 40 hr were observed. In contrast, the Q10 of the rhythm above 220C was 1.1, with circadian periods of [18][19][20][21] hr. Thus, cel displayed a threshold temperature or "break point" for the temperature compensation of its rhythm.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The Q10 of the rhythm below 220C was 2.2, and periods of about 40 hr were observed. In contrast, the Q10 of the rhythm above 220C was 1.1, with circadian periods of [18][19][20][21] hr. Thus, cel displayed a threshold temperature or "break point" for the temperature compensation of its rhythm.…”
mentioning
confidence: 78%
“…The possible involvement of membranes as a component ofcircadian rhythmicity was proposed by others (19) in part because of temperature compensation. Membrane "fluidity" is known to be temperature-compensated in a number of systems by means of alteration in fatty acid composition ("homeostasis of membrane fluidity") (20,21). If circadian kinetics were dependent on membrane fluidity, no additional temperature-compensation mechanism would need to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore began our study with an in vivo examination of membrane physical properties as inferred from freeze-fracture electron microscopy. The technique employed involved chilling several aliquots of cells, each to a different test temperature, before fixation with glutaraldehyde (7,9). The resuiting patterns of intramembrane protein particle distribution on the freeze-fracture replicas could be used to determine the temperature at which each membrane underwent initial phase separation of its constituent lipids (7).…”
Section: Tetrahymena Pyriforrnismentioning
confidence: 99%
“…One possibility is through changes in the membrane lipid composition. Much evidence has been accumulated to establish that Tetrahymena can alter its membrane fluidity very rapidly by producing specific lipid species on the endoplasmic reticulum and transferring them to other membranes (6,7,9). We modified one of these earlier experiments to test the ability of food vacuoles to respond to a fluidity-modifying stimulus.…”
Section: Figurementioning
confidence: 99%
“…2). It has also been shown that the membranes of Tetrahymena regulate their fluidity in response to changes in the ambient temperature (20,21,27). Thus, on increasing or decreasing the culture temperature, compensatory changes in the lipid composition of the membrane take place, and as a consequence the conformation of the membrane-associated proteins would be expected to change.…”
Section: Discussionmentioning
confidence: 99%